If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5)(x + 5) + 26 = 47 Reorder the terms: 3(5 + x)(x + 5) + 26 = 47 Reorder the terms: 3(5 + x)(5 + x) + 26 = 47 Multiply (5 + x) * (5 + x) 3(5(5 + x) + x(5 + x)) + 26 = 47 3((5 * 5 + x * 5) + x(5 + x)) + 26 = 47 3((25 + 5x) + x(5 + x)) + 26 = 47 3(25 + 5x + (5 * x + x * x)) + 26 = 47 3(25 + 5x + (5x + x2)) + 26 = 47 Combine like terms: 5x + 5x = 10x 3(25 + 10x + x2) + 26 = 47 (25 * 3 + 10x * 3 + x2 * 3) + 26 = 47 (75 + 30x + 3x2) + 26 = 47 Reorder the terms: 75 + 26 + 30x + 3x2 = 47 Combine like terms: 75 + 26 = 101 101 + 30x + 3x2 = 47 Solving 101 + 30x + 3x2 = 47 Solving for variable 'x'. Reorder the terms: 101 + -47 + 30x + 3x2 = 47 + -47 Combine like terms: 101 + -47 = 54 54 + 30x + 3x2 = 47 + -47 Combine like terms: 47 + -47 = 0 54 + 30x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(18 + 10x + x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(18 + 10x + x2)' equal to zero and attempt to solve: Simplifying 18 + 10x + x2 = 0 Solving 18 + 10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-18' to each side of the equation. 18 + 10x + -18 + x2 = 0 + -18 Reorder the terms: 18 + -18 + 10x + x2 = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 10x + x2 = 0 + -18 10x + x2 = 0 + -18 Combine like terms: 0 + -18 = -18 10x + x2 = -18 The x term is 10x. Take half its coefficient (5). Square it (25) and add it to both sides. Add '25' to each side of the equation. 10x + 25 + x2 = -18 + 25 Reorder the terms: 25 + 10x + x2 = -18 + 25 Combine like terms: -18 + 25 = 7 25 + 10x + x2 = 7 Factor a perfect square on the left side: (x + 5)(x + 5) = 7 Calculate the square root of the right side: 2.645751311 Break this problem into two subproblems by setting (x + 5) equal to 2.645751311 and -2.645751311.Subproblem 1
x + 5 = 2.645751311 Simplifying x + 5 = 2.645751311 Reorder the terms: 5 + x = 2.645751311 Solving 5 + x = 2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 2.645751311 + -5 Combine like terms: 5 + -5 = 0 0 + x = 2.645751311 + -5 x = 2.645751311 + -5 Combine like terms: 2.645751311 + -5 = -2.354248689 x = -2.354248689 Simplifying x = -2.354248689Subproblem 2
x + 5 = -2.645751311 Simplifying x + 5 = -2.645751311 Reorder the terms: 5 + x = -2.645751311 Solving 5 + x = -2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = -2.645751311 + -5 Combine like terms: 5 + -5 = 0 0 + x = -2.645751311 + -5 x = -2.645751311 + -5 Combine like terms: -2.645751311 + -5 = -7.645751311 x = -7.645751311 Simplifying x = -7.645751311Solution
The solution to the problem is based on the solutions from the subproblems. x = {-2.354248689, -7.645751311}Solution
x = {-2.354248689, -7.645751311}
| 5x-(3x+x)=2(2x+5) | | 19-1x=14 | | 34.9+y=13 | | 5a^5+20a^3-40a-25= | | 8+2x=21 | | 3(x+2.84)=2x | | 9+(x-4)=15 | | -7/963x | | x^2+0.755x-0.177=0 | | 9y=8(y+8) | | -1.6(2y+15)=-1.3(2y-10) | | 3(y-2)/5=-2y | | 2(x+4)-4= | | 7(7c-8)=41 | | 4x-8=35 | | 3(4x-8)=0.2(35x+30) | | 3(2x-5+31)=14 | | 1/4y7 | | 5x+6=5(x-9) | | x/3-(3x-7)/5=(x-2)/6 | | 3.2+x=3.4 | | 60/400 | | (56x^2-8x^3)/(x^2(7-x)) | | 5m+1=m^2-49 | | -2(5)+y=1 | | f(x)=2x^2-8x-10 | | 18=k(28) | | 140=30+5s | | 19=a-5.4 | | 3x^2+20x=-12 | | 16=2w+(-8)+10w-12 | | 9(12)+9(3)= |